Polygeline in patients with hypovolemia caused by accidental trauma: a prospective, multicentric, safety study - Shah, Sanjay; Singh, Ajai; Kala, Sanjay; Shetty, Rohita (International Surgery Journal, 2018)
Background: Objective of present study was to evaluate the safety of polygeline (Haemaccel®) and its effect on vital sign parameters in patients with hypovolemia caused by accidental trauma. Methods: Adverse drug reactions (ADRs) of polygeline within 6 hours after administration, and the effect of polygeline infusion on vital sign parameters, in trauma patients hospitalized at the emergency department, were evaluated in this prospective, multicentric, post-marketing observational study. Results: One hundred forty patients (men: 81.4%; women: 18.6%), with a mean (±standard deviation) age of 33.7±10.6 years, were enrolled. At the time of admission, mean blood volume loss was 1400.1±558.8ml, with 86.4% patients reporting blood volume loss of >15%; 49.3% patients presented with class-II hypovolemia. No ADRs or any unusual clinically significant changes were reported within 6 hours of polygeline administration. All vital parameters (blood pressure and pulse rate) significantly improved at 1 hour of polygeline administration; this trend was sustained until 6 hours (p<0.001). Reduction in respiratory rate was significant at 1 and 6 hours versus baseline (p<0.001). Urine output and central venous oxygen saturation also showed significant improvement at 1 and 6 hours after treatment initiation (p<0.001). Arterial pH and mean blood lactate levels also showed a significant change from the baseline (p<0.05) at both 1 and 6 hours. Conclusions: Polygeline was found to be safe and effective in improving hemodynamic stability in patients with hypovolemia due to accidental trauma.